Review of Some Methods for Improving Transient Response in Automotive Diesel Engines through Various Turbocharging Configurations - Giakoumis, Evangelos G. (Frontiers in Mechanical Engineering, 2016)
Turbocharged diesel engines suffer from poor drivability, mostly at low loads and speeds, leading also to overshoot in exhaust emissions (primarily PM/soot and NOx) during the transient operation after a speed or load increase. The main cause for this problematic behavior is located in the turbocharger in the form of high moment of inertia and unfavorable aerodynamic-type compressor flow characteristics. In the present work, various alternative turbocharging configurations are reviewed that have proven successful in improving the dynamic diesel engine operation. The configurations studied are: combined supercharging, variable geometry turbine, electrically assisted turbocharging, two stage series and sequential turbocharging, as well as lower turbine moment of inertia. It is shown that significant improvement in the engine’s transient response can be realized through reduction in the turbocharger mass moment of inertia (using lighter materials and/or more than one units). Increasing the available turbine torque (e.g. through elevated turbine back pressure in a variable-geometry turbine) is another successful option, as well as enhancement of the compressor boost pressure (e.g. through the use of a positive displacement compressor upstream of the turbocharger). Finally, the use of external energy (e.g. in the form of electrical assistance on the turbocharger shaft during the critical turbocharger lag phase) is another recently developed and highly promising measure to mitigate the drawbacks of the poor transient performance of turbocharged diesel-engined vehicles and limit their exhaust emissions.